Macular inner retinal layers in multiple sclerosis - Zahavi, Ori; Nilsson, Maria; Manouchehrinia, Ali; Brautaset, Rune; Kockum, Ingrid; Venkataraman, Abinaya P.; Dominguez-Vicent, Alberto (Frontiers in Neurology, 2025)
AimTo evaluate the structural changes of individual inner retinal layers in the macular area and identify the most affected layer in subgroups of multiple sclerosis (MS) patients compared to healthy controls (HC).MethodsIn total, Optical coherence tomography (OCT) data from 507 MS patients and 183 HC were exported retrospectively. The MS patients were grouped according to MS sub-types, primary progressive (PP), Relapsing–Remitting (RR) and Secondary progressive (SP). Thickness of four inner retinal layers, the macula nerve fiber layer (NFL), ganglion cell layer (GCL), inner plexiform layer (IPL) and the inner nuclear layer (INL) were evaluated in nine sectors based on the Early Treatment Diabetic Retinopathy Study (ETDRS) map. The individual layer thickness measurements were compared between each MS subtype and HC while controlling for the potential confounding effects of age, sex, and previous history of ON.ResultsThe NFL was thinner in all inferior, superior, and nasal sectors in all MS subgroups. The thinning was more pronounced in the PP and SP groups. The thinning varied between 3 to 20% compared to HC. The GCL was also thinner, especially in the inner sectors of the ETDRS grid. The SP subgroup had the largest reduction (27.8%) in the inner nasal sector. The IPL was also reduced in all MS subgroups. In contrast to PP and SP groups, the RR group showed an increased INL thickness compared to HC in the inner sectors.ConclusionMacular region is suitable for monitoring the neurodegeneration in MS. The macular NFL seems to have the strongest association with MS disease and may serve as a marker for global atrophy. The pattern of IPL reduction tends to follow the GCL, so these layers can be measured combined.